Screening of Pre- and Post-Emergence Herbicides for Weed Control in Camelina sativa (L.) Crantz - Si-Zhe Dai; Yawen Wang; Min-Jung Yook; Hui-Zhen Wu; Min Chen; Chuan-Jie Zhang (Agronomy)
Weed management has been one of the major challenges in camelina [Camelina sativa (L.) Crantz] production owing to the limited options for selective herbicides. The aim of this study was to evaluate and screen camelina-safe herbicides and establish an effective weed management program combining pre- and post-emergence herbicide application in camelina. There were 22 herbicides (6 herbicides registered as pre- and 16 herbicides registered as post-emergence herbicides) with various modes of action tested in this study. Greenhouse evaluation showed that, of the 22 herbicides tested, post-application of s-metolachlor and prodiamine (registered as pre-emergence herbicide), and clethodim, fluazifop-p, clopyralid, and quinclorac (registered as post-emergence herbicide) possessed adequate safety (~×4 of recommended doses) when used on the two camelina genotypes (CamC1 and CamK3) by evaluation of plant visual efficacy, seed weight, and plant biomass yield per plant. Herbicides from the ALS (e.g., flumetsulam), HPPD (e.g., mesotrione), IPP (e.g., clomazone), PPO (e.g., oxyfluorfen), and PS II (e.g., bentazon) groups caused severe camelina growth suppression and mortality. Field evaluation with greenhouse-selected herbicides demonstrated the superior weed control efficacy of sequential application combining pre- (s-metolachlor) and post-emergence (clethodim, fluazifop-p, or clopyralid) herbicides (84–90% reduction in weed biomass in camelina plots relative to untreated control) than the single application of those herbicides (68–83%). Clethodim and fluazifop-p provided good post-emerged grass weed control (e.g., crabgrass), whereas clopyralid effectively controlled the broadleaf weeds, such as common vetch and shepherd’s purse. Camelina seed yields from s-metolachlor following clethodim, fluazifop-p, or clopyralid application were statistically comparable to the yield of the weed-free treatment (hand weeding) and were significantly greater than those of the untreated control, indicating the effective weed control efficacies provided by those herbicides. Sequential application of the above herbicides did not affect camelina seed oil content, the principal UFA concentrations (e.g., C18:1~3), UFA/SFA, and MUFA/PUFA. In summary, sequential application combining pre- (s-metolachlor) and post-emergence (clethodim, fluazifop-p, or clopyralid) herbicides shows effective weed control in camelina, thus providing a great opportunity to increase camelina production through herbicide-based weed management.